Bilateral ischemic optic neuropathy with multiple cranial nerve palsies in giant cell arteritis - Richa Dhiman; Kuntal Patel; Nancy Sharma (Journal of Clinical Ophthalmology and Research)
A 66-year-old diabetic male presented to our center with a 3-day history of blurring of vision in the right eye, bilateral temporal headache, and diplopia. Fundus examination and optical coherence tomography revealed optic disc edema with optic atrophy of the left eye. The erythrocyte sedimentation rate and C-reactive protein levels were elevated. Color Doppler ultrasonography of the temporal artery revealed left-sided temporal artery wall thickening, which was suggestive of temporal arteritis. The patient was diagnosed with the right eye arteritic anterior ischemic optic neuropathy (A-AION) and the left eye posterior ischemic optic neuropathy (PION), with multiple cranial nerve palsies secondary to giant cell arteritis (GCA). There was a marked improvement in vision from finger counting to 6/36, with a significant improvement in headache after administering high-dose steroids. This case exemplifies the atypical presentation of GCA with bilateral vision loss due to PION in one eye and AION in the other eye if not diagnosed early.